Administering Medications - Gauwitz, Donna F. (McGraw-Hill, 2009)
Administering Medications : Pharmacology for health careers is designed to teach the safe administration of medications to health care students entering nursing, medical assisting, and other allied health care professions. This textbook speaks directly to students encourages student to identify and apply the concepts learned